WOMEN'S LOCAL KNOWLEDGE ON PLANT UTILIZATION AND ITS RELATION TO FOREST CONSERVATION IN THE WAN ABDUL RACHMAN FOREST PARK - Riniarti Melya; Inggar Damayanti; Dian Rahmalia (Jurnal Nusa Sylva, 2026)
The Tahura Wan Abdul Rachman area plays an important role in maintaining biodiversity and supporting the lives of the people of the buffer villages through various plant resources used in daily life. Local community knowledge of plant use is an important part of supporting forest conservation, especially through women's role as guardians of cultural and ecological knowledge. This research aimed to explore the role of women in preserving plant knowledge and forest conservation in Talang Mulya Village, a buffer village for Tahura WAR. The research was conducted using survey methods and semi-structured interviews with 65 female respondents. Data were analyzed descriptively, quantitatively, and qualitatively. The results showed that most respondents had high knowledge of the types of plants around the forest (83.10%), the traditions of plant use (90.77%), and the cultural and spiritual values associated with certain plants (78.46%). Most of this knowledge (75.38%) was obtained from parents and ancestors. Most respondents (57.11%) also replanted plants in the environment around their homes, although their involvement in formal forest conservation activities remained relatively low. This research shows that women play an important role in sustaining ethnobotanical knowledge and supporting local knowledge-based conservation in forest areas.